Human milk oligosaccharide profiles remain unaffected by maternal pre-pregnancy body mass index in an observational study - Astono, Julie; Huang, Yu-Ping; Sundekilde, Ulrik Kræmer; Barile, Daniela (Frontiers in Nutrition, 2024)
Human milk oligosaccharides (HMOs) are important carbohydrates in human milk that infants cannot digest, acting as prebiotics linked to infant health. The risk of childhood obesity increases with maternal obesity, potentially mediated through the gut microbiota affected by the available HMOs. Studies on whether maternal obesity affects HMO abundance, yield conflicting results. This study aimed to investigate the HMO profile and its association with maternal obesity measured by pre-pregnancy body mass index (BMI) and infant anthropometrics. The results were discussed in the context of existing literature. 90 human milk samples were collected at three months postpartum from mothers in three BMI-groups: 32 normal weight (BMI: 18.5-24.99 kg/m 2 ), 34 overweight (BMI: 25-30 kg/m 2 ), and 24 obese (BMI > 30 kg/m 2 ). The samples were analyzed using nano liquid chromatography chip quadrupole time-of-flight mass spectrometry yielding 51 HMO structures and isomers. Their peak areas were integrated and normalized to determine relative abundances. Univariate and multivariate analysis showed associations between relative HMO abundance and donors' secretor status and specific infant anthropometric variables, but not with maternal pre-pregnancy BMI. This study does not support the hypothesis that maternal overweight influences the HMO profile and highlights the importance of reporting results despite absence of significant correlations.